İslam ve kapitalizm: küresel bir bakış açısı ve Türkiye perspektifleri - Nagaoka, Shinsuke; Orhan, Zeyneb Hafsa; Şencal, Harun; Orhan, Zeyneb Hafsa (Kyoto University, 2021)
Kyoto University Islamic Economic Studies Project (KUISES), Graduate School of Asian and African Area Studies
Islam and capitalism: a global viewpoint and perspectives from Turkey
İslam ve Kapitalizm: Küresel Bir Bakış Açısı ve Türkiye Perspektifleri Nagaoka Shinsuke, ORHAN ZEYNEB HAFSA, ŞENCAL HARUN, Yayın Yeri:Kyoto University Islamic Economic Studies Project (KUISES), Graduate School of Asian and African Area Studies, Kyoto University, Basım sayısı:1, Sayfa sayısı:81, ISBN:978-4-910482-01-9,